Information in an Industrial Culture: Walter A. Shewhart and the Evolution of the Control Chart, 1917–1954. - Bradford, Phillip G.; Miranti, Paul J. (Information & Culture, 2019)
This study analyzes the factors that shaped Walter Shewhart's 1924 development of the control chart at Bell Telephone Laboratories. The control chart is a graphical construct that uses probability theory to analyze deviations from expected levels of performance within systems of repetitive action. Although Shewhart's innovative use of probabilistic information focused on monitoring conformity to production standards in mass manufacturing, his basic concepts continue to affect modernity through their extensive application in data analysis in business, engineering, and science.